Effect of bevel angles on tensile strength of SS304 steel weld joints - Pedapati, S.R. (Springer Heidelberg, 2017)
Welding is one of the most universal type of joining method used in the industry especially oil and gas industry. Good welding of pipe is crucial as bad welding can lead to cracks and failures. One of the parameter that affects the quality of weld is the bevel angle for single V butt joint weld. This paper aims to analyse the effect of different included bevel angle of SS304 stainless steel pipe weld. Simulation was performed in ANSYS which showed that 50-degree bevel angle is the optimum bevel angle for single V butt joint for SS304 steel with 13 mm thickness. To verify the simulation result, experiment was performed. The type of welding process that was used to perform the weld was Gas Tungsten Arc Welding (GTAW), also known as Tungsten Inert Gas (TIG) welding. The SS304 stainless steel was first sectioned and milled in order to achieve different bevel angle before being welded using TIG welding and machined again in order to perform tensile test. Tensile test was performed according to ASTM E8 standard in order to determine the strength of the welded pipe. Based on the values obtained from the tensile test such as Yield Strength and Ultimate Tensile Strength (UTS), the optimum bevel angle for single V butt joint is 50-degree. © Springer Nature Singapore Pte Ltd. 2017.